2010
DOI: 10.1002/asi.21295
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the syntactical and structural analysis of Library of Congress Subject Headings for the digital environment

Abstract: With the current information environment characterized by the proliferation of digital resources, including collaboratively created and shared resources, Library of Congress Subject Headings (LCSH) is facing the challenges of effective and efficient subject-based organization and retrieval of digital resources. To explore the feasibility of utilizing LCSH in a digital environment, we might need to revisit its basic characteristics. The objectives of our study were to analyze LCSH in both syntactic and relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…They show that the portion of LCSH assigned to our collection has 45% fewer orphans (39.8 − 21.7). This concurs with Yi and Chan (), who reported that the domain of science was the most connected portion of the LCSH structure.…”
Section: Methodssupporting
confidence: 92%
“…They show that the portion of LCSH assigned to our collection has 45% fewer orphans (39.8 − 21.7). This concurs with Yi and Chan (), who reported that the domain of science was the most connected portion of the LCSH structure.…”
Section: Methodssupporting
confidence: 92%
“…There are 20,791 MeSH descriptors assigned to the collection of 233,388 bibliographic records, and 18,318 LCSHs assigned to a collection comprising 122,197 bibliographic records housed in the McGill Schulich Science and Engineering library . The subset of LCSH representing the domain of science was selected for this study because it offers the most complex portion of the LCSH structure (Julien et al., ; Yi & Chan, ). Some subject headings not assigned to documents are required to connect the tree fully from the most general down to the most specific subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Data set characteristics. The subset of LCSH representing the domain of science was selected for this study because it offers the most complex portion of the LCSH structure(Julien et al, 2012a;Yi & Chan, 2010). Some subject headings not assigned to documents are required to connect the tree fully from the most general down to the most specific subjects.…”
mentioning
confidence: 99%
“…Our dataset is comprised of 1) a collection of 122,197 bibliographic records housed at McGill University's Schulich Library of Science and Engineering, and 2) its roughly 205,000 LCSH authority records. The domain of science was selected as an extreme test for this study since it offers the deepest and most connected portion of the LCSH structure (Julien, Tirilly, Leide, & Guastavino, 2012;Yi & Chan, 2010).…”
Section: Datasetsmentioning
confidence: 99%